Comparative Study of Contagious Diseases in Clay County vs. Riley County: Diphtheria, Scarlet Fever, Smallpox, Typhoid Fever, 1907-1917 - Musgrove, Yates S. (Kansas State University. Dept. of History, 2011)
Analyzing contagious disease records kept by physicians in two contiguous Kansas counties, this study reaches interesting conclusions about the role of the railroads in early twentieth century Kansas. Rail lines are suspected disease vectors. The presence of Kansas State University also played a part in the spread of specific contagious diseases. The author presents data in statistical tables.
Keywords: Clay County; Riley County; Diphtheria; Scarlet Fever; Smallpox; Typhoid Fever